2002
DOI: 10.1023/a:1020565523615
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A coupling of above-ground plant diversity and below-ground microbial diversity has been implied in studies dedicated to assessing the role of macrophyte diversity on the stability, resilience, and functioning of ecosystems. Indeed, above-ground plant communities have long been assumed to drive below-ground microbial diversity, but to date very little is known as to how plant species composition and diversity influence the community composition of micro-organisms in the soil. We examined this relationship in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(97 citation statements)
references
References 52 publications
7
89
1
Order By: Relevance
“…Some studies have shown that non-legume forbs can invest more long-term carbon storage into roots, reducing the amount of root exudation and potentially exerting a stronger selective force on rhizosphere communities compared to grass species [11,30,39]. Further grasses and forbs have distinct root architectures (fibrous vs. taproot, respectively), which can influence rhizosphere microbial communities [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that non-legume forbs can invest more long-term carbon storage into roots, reducing the amount of root exudation and potentially exerting a stronger selective force on rhizosphere communities compared to grass species [11,30,39]. Further grasses and forbs have distinct root architectures (fibrous vs. taproot, respectively), which can influence rhizosphere microbial communities [3].…”
Section: Discussionmentioning
confidence: 99%
“…Within this region, abiotic and biotic factors, such as rhizodeposition (including water-soluble exudates, sloughed cells and mucilage), water uptake, soil pH and competition for nutrients, create a unique environment for soil microbes compared to bulk soil [5][6][7][8]. The rhizosphere habitat commonly displays increased microbial biomass and activity, decreased diversity and microbial compositions that are distinct from those of the bulk soil [9][10][11][12]. This phenomenon is commonly referred to as the "rhizosphere effect" [1,3,13].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to DNA extraction, samples were washed with 20 mM K 2 PO 4 to remove extracellular DNA (Kowalchuk et al, 2002). DNA extracts were stored at āˆ’20 ā€¢ C. Real-time PCR was carried out to determine the relative abundance of the class 1 integronintegrase intl1 gene.…”
Section: Presence Of Contaminantsmentioning
confidence: 99%
“…Although all plants have speciesā€specific effects on soil they colonize (Bardgett & van der Putten, 2014; Berg & Smalla, 2009), invasive plants often appear to alter soils to their advantage, creating positive plantā€“soil feedback and promoting dominance (Berg & Smalla, 2009; Bever, 1994; Diez etĀ al., 2010; Fitzsimons & Miller, 2010; Flory & Clay, 2013; Klironomos, 2002; Kowalchuk, Buma, De Boer, Klinkhamer, & van Veen, 2002; Peterman, Fergus, Turnbull, & Schmid, 2008; van der Putten etĀ al., 2013; van Grunsven etĀ al., 2007). Soil biota contribute strongly to these plantā€“soil feedbacks, and seedling survival appears to be a critical demographic stage in determining invasive success (Blaney & Kotanen, 2001; Packer & Clay, 2000; Reinhart & Clay, 2009; Reinhart, Tytgat, van der Putten, & Clay, 2010).…”
Section: Introductionmentioning
confidence: 99%